2022
DOI: 10.1186/s40634-022-00446-2
|View full text |Cite
|
Sign up to set email alerts
|

Synovial mast cells from knee and hip osteoarthritis: histological study and clinical correlations

Abstract: Purpose The aim of this study was to investigate the presence of synovial mast cells (MCs) in hip and knee tissue from osteoarthritis (OA) patients and to correlate them with clinical and radiological data. Methods Synovial tissue was obtained during arthroplasty from 60 patients, 30 with knee OA and 30 with hip OA. Control synovial tissue was obtained from 30 patients without OA, 15 undergoing above-knee amputation and 15 receiving a hip replaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…There is always a significant knowledge gap in the literature concerning the selection of an appropriate control group for OA synovium and considerable ethical challenges to acquiring such samples ( 19 ). However, there are a number of approaches available to fill this gap including using synovial samples acquired from cadaveric joints ( 20 ), above-knee amputation ( 21 ), arthroscopy for the unspecified indication ( 22 ), or even from normal-appearing areas of synovium within an OA joint ( 23 ). In this study, the non-OA-diagnosed synovium was obtained from sports injury patients, mostly young athletes who have had their anterior crucial ligament reconstruction 6 months before their injury was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…There is always a significant knowledge gap in the literature concerning the selection of an appropriate control group for OA synovium and considerable ethical challenges to acquiring such samples ( 19 ). However, there are a number of approaches available to fill this gap including using synovial samples acquired from cadaveric joints ( 20 ), above-knee amputation ( 21 ), arthroscopy for the unspecified indication ( 22 ), or even from normal-appearing areas of synovium within an OA joint ( 23 ). In this study, the non-OA-diagnosed synovium was obtained from sports injury patients, mostly young athletes who have had their anterior crucial ligament reconstruction 6 months before their injury was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MCs and their degranulation products were observed in the SM and synovial fluid of KOA patients [ 26 ]. Moreover, the number of synovial MCs correlates with the KOA patients’ synovitis score [ 25 ]. As CD88 expression in MCs contributes to granulation [ 30 ], this evidence suggests that NMU/NMUR1-mediated activation of MCs, particularly CD88(+) MC subsets, may contribute to the synovial pathology in obese KOA patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being found in the synovial membrane (SM), MCs are elevated in patients with rheumatoid arthritis (RA) [ 19 , 20 , 21 ] and OA [ 22 , 23 , 24 ], suggesting that MCs could constitute a crucial component of the mechanism underlying both acute and chronic inflammation. More recent studies have demonstrated a potential association between MCs and knee OA (KOA) severity [ 25 , 26 ]. Given that we also previously reported increased MC marker expression in obese KOA patients [ 6 , 27 , 28 ], we hypothesized that MCs may contribute to the NMU/NMURs system in the osteoarthritic synovium of obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In chronically inflamed joints, the synovial membrane becomes hypertrophic and the MC density significantly increases, as a result of the recruitment of circulating progenitors, the maturation of local MC precursors, the differentiation of local mesenchymal stem cells (MSCs) into MCs, and the release of neurotrophins as NGF that stimulate further MC proliferation. Farinelli et al have recently shown, in hip and knee tissue from OA patients undergoing arthroplasty, a significant increase in the MCs and the vessel number, which significantly correlated with the synovitis score and disease severity [ 39 ]. The synovial MC infiltration has been associated with a variety of inflammatory changes which may play a role in the pathophysiology of OA [ 40 , 41 ].…”
Section: Role Of Mast Cells In Oamentioning
confidence: 99%